Dietary fibers in emulsified meat products - Pergat, Oleh; Strashynskyi, Igor; Pasichnyi, Vasyl; Semeniuk, A. (My University, 2023)
In comminuted meat products, the meat fibers are reduced in size thereby giving a tender texture. There are two ways to incorporate dietary fiber in meat products viz, formulation of a new product, and enrichment of existing products with minimum changes in their quality attributes. The most powerful tool used for texture analysis is the sensory texture profile analysis. У подрібнених м’ясних продуктах м’ясні волокна зменшуються в розмірі, що забезпечує ніжну текстуру. Існує два способи введення харчових волокон у м’ясні продукти, а саме: створення нового продукту та збагачення існуючих продуктів з мінімальними змінами їх якісних характеристик. Найпотужнішим інструментом, який використовується для аналізу текстури, є сенсорний аналіз профілю текстури.
Keywords: кафедра технології м’яса і м’ясних продуктів; якість м’ясних продуктів; dietary fibers; meat processing; quality of meat products; харчові волокна; обробка м’яса